THE ANALYSIS OF SPEECH FEATURES OF FEMALE CHARACTERS IN GOSSIPING (A STUDY CASE IN THE FILM â€œBRIDESMAIDSâ€) - Paderan, Mark Philip C.; Alrajafi, Gali; Eryon, Eryon (Universitas Muhammadiyah Lampung, 2023)
This research focuses on analyzing the speech features in gossiping produced by the female characters, of the Film â€œBridesmaidsâ€ in which the settings are a house, apartment, and restaurant.Â The theories used are Joneâ€™s theory about gossiping, and Lakoff and Holmeâ€™s theory of female speech features and social factorsÂ The descriptive qualitative method is used in this study as the research method since the numbers are not the form of the data but in the forms of utterances. This study aims to answer the problem of what speech features are used in gossiping.Â Â This study found that the topic that is mostly revealed gossiping is house talk and the most speech features used is swearing and many produced in topics of gossiping â€˜bitchingâ€™.